Econometric Analysis between Spot and Futures Market in Indian Derivative Segment - Rajani B. Bhat and Suresh V. N (Commerce Spectrum, 2014)
Johansen’s Co-integration technique followed by the Granger Causality test was employed to examine the relationship between NSE spot and futures market for selected scrip of Nifty of NSE. An empirical analysis was conducted for the closing price of near month prices from 9 th November 2001 to 31 st March 2012 and it is collected from National Stock Exchange (NSE) website. The analysis revealed that there exists a bi-directional causal relationship between spot and futures derivative market. Also an existence of co-integration between spot and futures market is also implied.